Imperial Vision in the Arctic: Fleeting Looks and Pleasurable Distractions in Barker’s Panorama and Shelley’s Frankenstein - Garrison, Laurie (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2008)
AbstractThe early nineteenth century saw a rebirth of British arctic exploration and the enthusiasm inspired by these new, seemingly benign imperial endeavors spread quickly and thoroughly through the popular press. One of the most popular media for conveying the news and results of imperial projects was Barker’s panorama in Leicester Square. This medium encouraged a form of vision that was particularly conducive to garnering public support; the overwhelmingly large and meticulously detailed canvases caused the viewer to engage in a swift, haphazard form of looking that conveniently drew focus away from all the potential violations of people, landscape and property implied in exploration of regions such as the Arctic. Mary Shelley’s Frankenstein, published just before the exhibition of Barker’s first arctic panorama, presents a critique of this form of vision in the arctic frame narrative, which is plagued by Captain Walton’s continually distracted looks.